CD86 +1057G>A Polymorphism and Susceptibility to Acute Kidney Allograft Rejection (Iranian Journal of Kidney Diseases, 2011)
Introduction. CD86 is a costimulatory molecule that participates in the regulation of T-cell lymphocytes activation. Thus, we examined a genetic marker on the CD86 gene in kidney transplant outcome.Materials and Methods. In our retrospective study, 168 kidney allograft recipients were genotyped by direct sequencing. Patients were classified into 2 groups of 29 human leukocyte antigen (HLA)-identical haplotype allograft recipients and 139 recipients showing one or more mismatches in the HLA haplotype. Forty-five patients (26.8%) developed at least 1 acute rejection (AR) episode, 7 in the first and 38 in the second group.Results. Acute rejection was associated with the presence anti-HLA antibodies before transplantation (P = .03). The AA genotype and A allele at position +1057 in the CD86 gene were more frequent in patients without AR (9.75% and 28.5%, respectively) compared with those showing an AR (2.22% and 23.3%, respectively). This difference was statistically significant in the anti-HLA-positive recipients, as AA frequency was 31.3% in non-AR patients and zero in AR ones (P = .04) and A allele frequency was 46.9% and 20.8%, respectively (P = .04). Patients bearing AA genotype reached a higher graft survival time (9.84 years) than those carrying GA (8.21 years, P = .32) or GG (7.61 years, P = .72) genotypes.Conclusions. These results suggest that AA genotype and A allele of CD86 +1057G>A polymorphism may confer a protection against acute kidney allograft rejection in Tunisian patients.